2019
DOI: 10.1080/03081087.2019.1586824
|View full text |Cite
|
Sign up to set email alerts
|

A complete characterization of smoothness in the space of bounded linear operators

Abstract: We completely characterize smoothness of bounded linear operators between infinite dimensional real normed linear spaces, probably for the very first time, by applying the concepts of Birkhoff-James orthogonality and semi-inner-products in normed linear spaces. In this context, the key aspect of our study is to consider norming sequences for a bounded linear operator, instead of norm attaining elements. We also obtain a complete characterization of smoothness of bounded linear operators between real normed lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The main objective of the present article is to study smoothness in the space of bounded linear operators on a Banach space, induced by the numerical radius. The study of smoothness in the space of bounded linear operators on a Banach space, with respect to the usual operator norm, is a classical area of research in geometry of Banach spaces [1,[6][7][8]12,[15][16][17][18]24,25]. The space of bounded linear operators on a Banach space, endowed with the numerical radius norm, need not be isometrically isomorphic to the space of bounded linear operators on the same Banach space, endowed with the usual operator norm, in general.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main objective of the present article is to study smoothness in the space of bounded linear operators on a Banach space, induced by the numerical radius. The study of smoothness in the space of bounded linear operators on a Banach space, with respect to the usual operator norm, is a classical area of research in geometry of Banach spaces [1,[6][7][8]12,[15][16][17][18]24,25]. The space of bounded linear operators on a Banach space, endowed with the numerical radius norm, need not be isometrically isomorphic to the space of bounded linear operators on the same Banach space, endowed with the usual operator norm, in general.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the norm attainment set of a linear operator T plays a pivotal role in determining the smoothness of T in L(X). A characterization of smoothness without any restriction on M T was provided in [24]. The above studies motivate us to explore the concept of numerical radius smoothness in (L(X)) w .…”
Section: Introductionmentioning
confidence: 99%
“…James [3,4] used it extensively in his study of geometric properties of normed linear spaces like smoothness and strict convexity. Recent studies [6,1,8,12,11] of this phenomenon in the context of operator theory have revealed a lot about the geometry of linear operators. Indeed, if T and U be a pair of bounded linear operators on a Banach space B over F(R or C), we say T ⊥ B U if ||T + λU || ≥ ||T || for all λ ∈ F, where ||.|| denotes the usual operator norm.…”
Section: Introductionmentioning
confidence: 99%
“…To do so we will use norm attainment set of an operator defined as : For T ∈ L(X, Y), the norm attainment set, denoted as M T , is the collection of all unit vectors at which T attains its norm, i.e., M T = {x ∈ S X : T x = T }. To look into the properties of norm attainment set and its role in the study of smoothness of operators one may go through [11,12,15,17].…”
Section: Introductionmentioning
confidence: 99%